PENERAPAN METODE AGILE DALAM MANAGEMEN PROYEK TEKNOLOGI INFORMASI - Bastian Aji Prihantoro; Ariska Fauzi; Dennis Eka Putra; Muhammad Chandra; Rizky Ashiddiqia (CV. Multi Kreasi Media, 2024)
The development of information technology and the management of future information technology projects can help practitioners and academics to understand more about the application of agile methods in the management of information technology projects. It is also hoped to provide insights into how the management of information technology projects can be integrated with agile methods so that they can help improve efficiency and be effective but, to implement agile methods in information technology projects effectively, strong project management skills, active involvement of clients, and appropriate adaptation to the project.